Optimal Selection of Imaging Examination for Lymph Node Detection of Breast Cancer With Different Molecular Subtypes - Zheng, Mingjie; Huang, Yue; Peng, Jinghui; Xia, Yiqin; Cui, Yangyang; Han, Xu; Wang, Shui; Xie, Hui (Frontiers in Oncology, 2022)
Objective Axillary lymph node management is an important part of breast cancer surgery, the accuracy of preoperative imaging evaluation can provide adequate information to guide operation. Different molecular subtypes of breast cancer have distinct imaging characteristics. This article was aimed to evaluate the predictive ability of imaging methods in accessing the axillary lymph node status in different molecular subtypes. Methods From 2013 to 2018, 2340 patients diagnosed with primary invasive breast cancer after breast surgery in Jiangsu Breast Disease Center, the First Affiliated Hospital with Nanjing Medical University were included. We collected lymph node assessment results from mammograph, ultrasound, and MRI, performed receiver operating characteristic (ROC) analysis, and calculated the sensitivity and specificity of each test. The C-statistics among different imaging models were compared in different molecular subtypes to access the predictive abilities of these imaging models in evaluating the lymph node metastasis. Results In Her-2 + patients, the C-statistics of ultrasound was better than that of MRI (0.6883 vs. 0.5935, p=0.0003). The combination of ultrasound and MRI did not raise the predict ability than ultrasound alone (p=0.492). In ER/PR+HER2- patients, the C-statistics of ultrasound was similar with that of MRI (0.7489 vs. 0.7650, p=0.5619). Ultrasound+MRI raised the prediction accuracy than ultrasound alone (p=0.0001). In ER/PR-HER2- patients, the C-statistics of ultrasound was similar with MRI (0.7432 vs. 0.7194, p=0.5579). Combining ultrasound and MRI showed no improvement in prediction accuracy than ultrasound alone (p=0.0532). Conclusion From a clinical perspective, For Her-2+ patients, ultrasound was the most recommended examination to assess the status of axillary lymph node metastasis. For ER/PR+HER2- patients, we suggested that the lymph node should be evaluated by ultrasound plus MRI. For ER/PR-Her2- patients, ultrasound or MRI were both optional examinations in lymph node assessment. Furthermore, more new technologies should be explored especially for Her2+ patients to further rise the prediction accuracy of lymph node assessment.